Kavouras, Panagiotis - (:unkn) unknown (My University, 2026)
A Physicist by degree, with an MSc in Materials Science and Technology and a PhD in Physics focused on Technology of Materials. Currently, his main research interests are characterization of mechanical properties with indentation methods at various length scales and the built up of a metrological approach for the calculation of Surface Free Energy through nano-indentation. His early career research interest was synthesis and characterization of vitreous and glass-ceramic silica-based materials for industrial solid waste management. He is the author of 42 published papers (38 ISI), 1 book chapter, 1 textbook. He has participated in 63 scientific conferences and workshops. Another side of his activities in funneled through his participation in four H2020 “Science with and for Society" projects, while he has participated in a Tender project related with Dual Use research in key enabling technologies. He is one of the contact persons and member of the coordinating team of Ethical Aspects in Research and Technology for Human network (EARTHnet), member of the European Network of Research Integrity Offices (ENRIO), through his participation in EARTHnet and member of the European Network for Ombuds in Higher Education (ENOHE).